Alineamiento de las acciones de RSE hacia la comunidad con las orientaciones de la guía ISO 26.000 en Uruguay (2020)
Various sources of information show that there is a group of companies in Uruguay that are actively working to incorporate CSR into their management, through the introduction of socially responsible behaviors in their labor, commercial, productive, environmental practices and relations with the Community in the that operate. However, there is no empirical research to determine if these behaviors are aligned with the guidelines of the ISO Guide 26,000 on Social Responsibility of organizations. In particular, it is unknown if these companies are applying the guidelines of this guide established in the chapter called Active Participation and Community Development. The results of a research on the activities of these companies in the field of CSR towards the Community are presented, with the aim of analyzing if they fit within the guidelines formulated in said chapter. A structured questionnaire was used, which was applied to those responsible for leading those activities in an intentional sample of that universe. It was found that, in general, the management and implementation of community support activities of these companies are aligned with the guidelines of ISO 26,000, despite the fact that a significant proportion of those interviewed admitted having little knowledge of these guidelines.